Assessment of the effects of forest fragmentation on aerial insectivorous bats in the Amazonian rainforest - López-Baucells, Adrià (2020)
Land use change and habitat fragmentation are among the most severe threats to biodiversity, especially in the tropics. In the Amazon, the abandonment of formerly deforested areas allowed the expansion of secondary regrowth, a type of habitat where bats are known to provide important ecosystem services. Amongst them, aerial insectivorous bats have been neglected in most Neotropical studies and remain poorly studied. However, the current upsurge in acoustic technology makes them easy targets to be monitored using ultrasound detectors. The aim of this thesis was to reveal the diversity of aerial insectivorous bats and quantify the effects of forest fragmentation on this ensemble within the Biological Dynamics Forest Fragments Project, a whole ecosystem experiment in the Amazon, currently composed of a mosaic of unflooded rainforest with continuous forest, and forest fragments embedded in a matrix of secondary regrowth. As part of this thesis, the first “Field Guide to the Bats of the Amazon” was published. A custom-built classifier was developed which was able to identify a large proportion of files to sonotype level (with > 90% accuracy), leaving the rest (<25%) to be manually classified. I also tested 20 different recording schemes and provided guidelines to optimize protocols for acoustic studies. In forest fragments and their adjoining secondary forests, taxonomic, phylogenetic and functional α diversity became gradually poorer with decreasing fragment size. In terms of β diversity, bat assemblage composition in secondary forests after ~30 years of recovery was still significantly different from that in continuous forest. However, forest edges harboured highly diverse bat assemblages due to the opening of cluttered areas, and the increase of less-sensitive species. Responses towards fragmentation were species-specific and strongly related to their functional traits. The results of this thesis highlight the irreplaceable value of tropical primary forests due to the long time required to recover fragmented ecosystems.